Creating Tunable Mesoporosity by Temperature‐Driven Localized Crystallite Agglomeration (Small 7/2022). Issue 7 (17th February 2022) - Jeong, Seok; Sim, Youjung; Kim, Jin Kyun; Shin, Sunyoung; Lim, Jaewoong; Seong, Junmo; Lee, Seonghwan; Moon, Dohyun; Baek, Seung Bin; Kim, Chae Un; Ryu, Ja‐Hyoung; Lah, Myoung Soo
Abstract : Tunable Mesoporosity In article number 2107006, Chae Un Kim, Ja‐Hyoung Ryu, Myoung Soo Lah, and co‐workers synthesize a tunable mesoporous metal‐organic framework that can be used for enzymatic immobilization through heat treatment of highly mosaic crystals with low‐density crystallites through localized agglomeration of volume‐reduced crystallites.